Serial high-sensitivity troponin I monitoring as a prognostic marker in acute ischemic stroke - Chandrasekaran, Nirmala Devi; P.V., Abinaya; Tazeem, Mohammed Suhail; K., Parameswaran; Venkatesan, Dev Sudersan; Ramalingam, Dhivakar; Mohan Rao, Velure Raja Rao (Rzeszów University Press, 2026)
Introduction and aim. Acute ischemic stroke (AIS) is a complex disease with multifactorial etiologies, often masking underlying cardiovascular morbidities that contribute to clinical outcomes. This study explored the role of serial high-sensitivity troponin I (hs-TnI) monitoring in AIS patients as a prognostic marker of cardiovascular morbidity and mortality. The results offer substantial information on the relationship between hs-TnI elevations and clinical, electrocardiographic (ECG), echocardiographic (ECHO), and angiographic parameters in patients with AIS. Material and methods. A prospective observational study was conducted on 60 patients with AIS in a tertiary care center, Tamil Nadu. Hs-TnI levels were measured at the time of admission and after 48 h together with ECG, ECHO. Angiographic evaluations were done in patients with elevated hs-TnI at 48 h after admission. Results. Among the study population, hs-TnI levels increased significantly from 11.7% at admission to 20% after 48 h (p=0.02).Logistic regression showed hs-TnI at 48 h predicted mortality (odds ratio [OR]=28.5, 95% confidence interval [CI]: 5.9‒137.1, p<0.001) and coronary artery disease (CAD) (OR=48.2, 95% CI: 9.8‒236.5, p<0.001). Conclusion. Serial monitoring of hs-TnI in AIS patients revealed its potential role in the identification of culprit lesions on coronary angiogram, which is correlated with the presence of CAD and mortality.
The study adhered to the guidelines set forth in the Declaration of Helsinki, and the protocol was approved by the Ethics Committee of the Institutional Ethics Committee of Chettinad Hospital and Research Institute, Tamil Nadu, India (074/IHEC/2020).
Keywords: acute ischemic stroke; cardiac mortality; high-sensitivity troponin I